Dependency of Pavement Roughness Level on the Type of Road Works - Paulius Paplauskas; Audrius Vaitkus (The Baltic Journal of Road and Bridge Engineering)
Managing the condition of the road network is essential to ensure sustainable and efficient road maintenance and development. The term asset management is broad, it describes the actions of infrastructure management – the activities associated with structure maintenance and operation, asset improvement, and development. The article analyzes the impact of the road works on the reduction of Road Roughness Index (IRI) depending on the road type and the type of repair. The annual change in IRI is estimated taking into account certain conditions - pavement structure class, road type, heavy traffic flow, repair type. The research analyzes the data of control assurance protocols of road sections repaired in 2008–2016 and the data of routine pavement performance surveys of the Lithuanian road network conducted in 2019. The results of the research are of considerable practical significance, it is recommended to include them in the repair selection module used by the Lithuanian pavement management system.